2001
DOI: 10.1046/j.1365-2648.2001.01780.x
|View full text |Cite
|
Sign up to set email alerts
|

Power and self‐perceived health in blind diabetic and nondiabetic individuals

Abstract: One way of improving health in diabetic blind individuals could be to increase the subject's perception of power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Across a range of measures, lower scores of quality of life were found in those with visual impairment,50 such as those with bilateral visual impairment being four times more likely to report “not feeling full of life” (OR=4.63, +9.47%) 51. Life satisfaction was higher in those with positive versus negative changes in views towards the world and themselves (self-esteem) 41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across a range of measures, lower scores of quality of life were found in those with visual impairment,50 such as those with bilateral visual impairment being four times more likely to report “not feeling full of life” (OR=4.63, +9.47%) 51. Life satisfaction was higher in those with positive versus negative changes in views towards the world and themselves (self-esteem) 41…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies that used the NEI-VFQ found those with visual impairment reported an average mean score of 81.68/100 (51–96/100), which was modestly but significantly lower than controls (average MD=10.32/100, range=0.45–26.40/100, R 2 =0.29–0.30),32 34 42 43 45–47 and those reporting depressive symptoms had worse scores (MD=7.2/100 to 15.5/100) 32 43. For the four remaining studies, a range of scales were used that found either non-significant or minimal differences in social functioning within groups or when compared to controls 36 48 50 52…”
Section: Resultsmentioning
confidence: 99%
“…Concordance with the recommendations of health care professionals for blood glucose control and lifestyle management may prove more difficult, if the individual is grappling with vision loss. In one study comparing visually impaired individuals with and without DM, participants with DM reported poorer general health, less satisfaction with physical health, and more negative feelings generally (Leksell, Johannsson, Wibell, & Wikblad, 2001). The term ‘psychological insulin resistance’ has been used to describe the ways in which fears and psychological barriers associated with diabetes treatments and lifestyle changes impact upon glycaemic control (Brod, Kongsø, Lessard, & Christensen, 2009; Skinner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based on her results, the power of nursing as a profession is linked to a number of factors including its status as a profession, the fact that the majority of its members are women and the extent to which nurses have knowledge and skills necessary to working with other disciplines. While Leksell et al (2001) have defined power as conscious choosing and doing intentionally [15], some authors believe that the source of power in the health system is authority. However, Kuokkanen (2001) has stipulated that power is more than controlling actions; it is the manipulation of thoughts, attitudes and social relations [16].…”
Section: Introductionmentioning
confidence: 99%